Influence of leachates produced by urban waste dumps on the water quality and possible risks to public health - Robert Christel Edzoa; Michel Bertrand Mbog; Vivien Piercy Lotse Tedontsah; Lionel Bitom Mamdem; Gilbert François Ngon Ngon; Bernard Tassongwa; Dieudonné Bitom; Jacques Etame; Kevin Djatsa Nguedia (Water Practice and Technology, 2024)
The aim of this study was to determine the impact of leachates, produced by one of Cameroon's largest waste dumps (Nkolfoulou), on the water quality and the risks posed to public health. A cartographic analysis was carried out, comparing the land use in the area before the landfill was setup with that of the present day, followed by a hydrogeological study of the groundwater and an analysis of trace metals. A model estimating susceptibility to pollution was developed using the Analytic Hierarchy Process (AHP) method, and this susceptibility was mapped using the previously developed model, which was validated. Land use increased by 57% between 1985 and 2023. Most of the landfill leachate is discharged untreated into the Foulou and Kondi rivers, polluting surface waters. Average levels of trace metal elements such as Cd and Mn are 2 and 3.24 mg/l, respectively, in groundwater, 72.62 and 8.54 mg/l, respectively, in surface water, and 114, 49 and 15.41 mg/l in leachate. The model developed, which takes into account factors such as depth, distance, and geomorphology in brief, is consistent and valid for the study. This is followed by the mapping of the impact zone showing wells, with high copper concentrations in high-susceptibility areas. HIGHLIGHTS The factors such as water depth, distance from the landfill, and geomorphological situation of the structures that are taken into account in the multiple analysis of the AHP criterion are validly consistent.; The three factors taken into account contributed to the development of an abbreviated point source pollution assessment method (PDG).; The method (PDG) is valid for estimating the susceptibility.;